Circular Storage Tanks and Silos - Ghali, Amin. (Boca Raton : CRC Press, 2014)
Preface to third edition: This book, now in its third edition, is a guide for analysis and design of circular storage tanks and silos. Recommended practice for design and construction of concrete water tanks and liquefied natural gas tanks is presented in a new chapter. A Web site companion of the third edition provides the computer program CTW (Cylindrical Tank Walls) to perform the analysis for the load combinations anticipated in the design of cylindrical prestressed walls. The analysis in the design of tanks or silos having the general shape of axisymmetrical shell can be performed by the finite-element computer program SOR (Shells of Revolution), which is available from the same Web site (http://www.crcpress.com/product/isbn/9781466571044). Like the earlier editions, the new edition is suitable for use by practicing engineers, students, and researchers in any country. No specific system of units is used in most solved examples. However, it is advantageous to use actual dimensions and forces on the structure in a small number of examples. These problems are set in SI units and Imperial units (still used in the United States); the answers and the graphs related to these examples are given in the two systems. The presented methods of analysis and design procedures are independent of codes. However, occasional reference is made to North American and European codes. Periodic revisions of the codes should not lessen the relevance of the presented material. For the analysis of a symmetrically loaded cylindrical wall, it is sufficient to consider an elemental strip parallel to the cylinder axis--
part 1. Analysis and recommended practice -- part 2. Design tables.
Includes bibliographical references and index.
Also available in print format.
Keywords: Storage tanks -- Design and construction; Silos -- Design and construction; Cylinders; Electronic books